Influence of Organized vs Non Organized Physical Activity on School Adaptation Behavior - Mosoi, Adrian A.; Beckmann, Jürgen; Mirifar, Arash; Martinent, Guillaume; Balint, Lorand (Frontiers in Psychology, 2020)
It is now well established that physical activity has positive effects on physical and mental health. However, the influence of organized physical activity (i.e. programs controlled and supervised by a trainer) on school adaptive behavior of adolescents with disabilities and/or behavioral remains unclear. A cross sectional study was conducted to test the effects of organized physical activity after school program that was controlled and supervised by a trainer on adolescents’ school behaviour adaptation which involves the ability to learn, conform to school norms and manage school activities without major behaviour conflicts. Eighty Romanian adolescents were recruited and allocated to three groups: a) with disabilities (Ds; N = 17, Mage = 14.55 years [SD = 1.16], 12 males and 5 females), b) with conduct disorders (CDs, N = 21, Mage = 14.52 years [SD = 1.11] 16 males and 5 females), and c) participants who had not shown signs of conduct disorders or disabilities (as a control group; N = 42, Mage = 14.2 years [SD = .46] 20 males and 22 females). Personality traits, school behaviour, and sensorimotor coordination were assessed by using Eysenck personality questionnaire - junior scale, school in-adaptability questionnaire scale, and Vienna test sport system (sensorimotor coordination test) respectively. Multivariate analysis of variance MANOVA (3 x 3) and discriminant analysis were used to examine differences on the psychological and sensorimotor coordination outcomes across three groups and three types of physical activity context: a) organized physical activity, b) non organized physical activity, and c) no physical activity. The findings indicate that not participating in an organized physical activity program results in a reduced level of physical mobility and consequently leads to maladaptive social and psychological outcomes. Thus, we argued that attending in an organized physical activity program is more beneficial for participants with disabilities and/or behaviour disorders, due to an increase in the probability of school integration and development of their motor skills. Clearly more research is needed in order to investigate these effects in neurophysiological levels.